Fourier and Anarchism - Mason, E. S. (Quarterly Journal of Economics, 1928)
I. Revolutionary groups in their attitude to science. Pretensions of anarchism to scientific method, 229. — II. Social sciences and modern anarchism draw from a common source, the conception of natural law, 231. — Ways in which this conception has been used, 235. — Reasons for the sharp divergence of anarchism from the point of view of students of the social sciences, 237. — III. Fourier's system is essentially anarchistic, 241. — The characteristics of his anarchism in its use of the idea of a natural order, 243.—The natural order of Fourier as an equilibrium of passional attractions, 250. — IV. Distinctiveness of Fourier's anarchism. His romanticism, 156. — His modernism, 260. — Criticism and summary, 261.